Sustainable MICE Event Practices: An Explorative Study - Raden Ayu Trisnayoni; I Putu Astawa; I Ketut Sutama (International Journal of Travel, Hospitality and Events, 2022)
ABSTRACT Purpose: This research aims to provide insight into sustainable event practices implemented by Melali MICE as one of the largest event organizers in Bali, Indonesia. Research methods: The research uses a qualitative approach. The sampling used is purposive. The informant selected as a sample is considered to know the sustainability and organizing of the event. Data collection using in-depth interview methods and participatory observations of the event at Melali MICE. Results and discussion: The cost is high to meet the needs of a green environment and to meet the demands of clients who are not environmentally friendly. This makes Melali MICE less likely to implement sustainability practices in the events they organize Implication: Planning for environmentally friendly events is needed to prepare for pre-event, event and post-event consistently implement sustainability practices. Keywords: event, event organizer, MICE, environmental sustainability.